Prenatal genetic counselors' perceptions of the impact of abortion legislation on counseling and access in the United States. Issue 6 (6th June 2021) - Jayaraman, Susheela; Koenig, Shelby; Fiddler, Morry; Simi, Eve; Goldenberg, Aaron; Magasi, Susan; Wicklund, Catherine
Abstract: Genetic counselors have an important role in offering and appropriate coordinating abortion services for patients identified with a fetal abnormality. Few studies have been conducted to determine the effects of legislation on genetic counselors and patients. This study aimed to further our understanding of genetic counselors' perception of the impact of abortion regulations on their practice, the perceived financial and emotional impact on their patients and their ability to access abortion. A 22‐question survey was developed based on themes identified by a qualitative study (Koenig et al., 2019, Journal of Genetic Counseling, 28, 790–801), and distributed to members of the National Society of Genetic Counselors; data from 113 respondents are analyzed. For analysis, participants were categorized into three groups based on the restrictiveness of their state's abortion legislation (supportive, middle ground, hostile) using the Guttmacher Institute's designation based on the amount of restrictive abortion legislation in their state. Participants reported that legislative gestational age restrictions significantly impact their counseling and coordinating of abortion services. Participants reported emotional and financial burdens that impact their patients seeking abortion; however, those in hostile states were significantly more likely to report a perceived financial or emotional impact on their patients. Participants in hostile states were more likely than those in supportive states to report that many of the addressed legislative and institutional regulations impact patients' ability to access abortion. Abortion regulations limiting the decision‐making time frame for patients with a fetal abnormality have a significant impact on the practice of prenatal genetic counseling. Further restrictions may change how genetic counselors choose to counsel their patients about the option of abortion, but also may limit the availability of choices particularly for patients in rural areas, in hostile states, and those without the financial resources to travel or pursue termination at later gestational ages.